KONSTRUKSI CITRA PEREMPUAN DALAM MEDIA ONLINE (Analisis Framing Rubrik Fashion Website Wolipop) - Lestarysca Lestarysca; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2013)
Wolipop is pages that presenting news or lifestyle articles about women, including the fashion rubric discussing the aspect of fashion from within the country and overseas which becomes a trend to date. As an online media which broadcasts information to the public, wolipop also features images of women which can be a reference to those who read it. This research is qualitative research that uses a method of William A. framing analysis. Gamson and modgliani argued that the frame is the way to talk, which presents construction meaning over events pertaining to an object of a discourse. The technique of collecting data used in this research is: documentary study of the primary data by collecting articles written on the fashion rubric of Wolipop from May 13 to 17, and also may 19, 2013. The news articles observed were selected based on the number of visitors every day. The result shows that wolipop always constructs women as figures who always want to look young, figures who can be influenced, figures of fashion adicts who shop high value goods although the goods are not very important. Lastly, wolipop gives images of women as tough figures who dare to demand their rights, try to seek freedom and refuse to be pre-sighted.